Village health worker motivation for better performance in a maternal and child health programme in Nigeria: A realist evaluation. Issue 3 (July 2022) - Mbachu, Chinyere; Etiaba, Enyi; Ebenso, Bassey; Ogu, Udochukwu; Onwujekwe, Obinna; Uzochukwu, Benjamin; Manzano, Ana; Mirzoev, Tolib
Background: Community health workers play an important role in linking communities with formal health service providers, thereby improving access to and utilization of health care. A novel cadre of community health workers known as village health workers (VHWs) were recruited to create demand for maternal health services in the Nigerian Subsidy Reinvestment Programme (SURE-P/MCH). In this study, we investigated the role of contextual factors and underlying mechanisms motivating VHWs. Methods: We used realist evaluation to understand the impact of a multi-intervention maternal and child health programme on VHW motivation using Anambra State as a case study. Initial working theories and logic maps were developed through literature review and stakeholder engagement; programme theories were developed and tested using focus group discussions and in-depth interviews with various stakeholder groups. Interview transcripts were analysed through an integrated approach of Context, Mechanism and Outcomes (CMO) categorisation and connecting, and matching of patterns of CMO configurations. Motivation theories were used to explain factors that influence VHW motivation. Explanatory configurations are reported in line with RAMESES reporting standards. Results: The performance of VHWs in the SURE-P maternal and child health programme was linked to four main mechanisms of motivation: feelings of confidence, sense of identity or feeling of acceptance, feeling of happiness and hopefulness/expectation of valued outcome. These mechanisms were triggered by interactions of programme-specific contexts and resources such as training and supervision of VHWs by skilled health workers, provision of first aid kits and uniforms, and payments of a monthly stipend. The monthly payment was considered to be the most important motivational factor by VHWs. VHWs used a combination of innovative approaches to create demand for maternity services among pregnant women, and their performance was influenced by health system factors such as organisational capacity and culture, and societal factors such as relationship with the community and community support. Conclusion: This paper highlights important contextual factors and mechanisms for VHW motivation that can be applied to other interventions that seek to strengthen community engagement and demand creation in primary health care. Future research on how to sustain VHW motivation is also required.